CDC42 switches IRSp53 from inhibition of actin growth to elongation by clustering of VASP - Disanza, Andrea; Bisi, Sara; Winterhoff, Moritz; Milanesi, Francesca; Ushakov, Dmitry S; Kast, David; Marighetti, Paola; Romet-Lemonne, Guillaume; Müller, Hans-Michael; Nickel, Walter; Linkner, Joern; Waterschoot, Davy; et al. (The EMBO journal, 2013)
Filopodia explore the environment, sensing soluble and mechanical cues during directional motility and tissue morphogenesis. How filopodia are initiated and spatially restricted to specific sites on the plasma membrane is still unclear. Here, we show that the membrane deforming and curvature sensing IRSp53 (Insulin Receptor Substrate of 53?kDa) protein slows down actin filament barbed end growth. This inhibition is relieved by CDC42 and counteracted by VASP, which also binds to IRSp53. The VASP:IRSp53 interaction is regulated by activated CDC42 and promotes high-density clustering of VASP, which is required for processive actin filament elongation. The interaction also mediates VASP recruitment to liposomes. In cells, IRSp53 and VASP accumulate at discrete foci at the leading edge, where filopodia are initiated. Genetic removal of IRSp53 impairs the formation of VASP foci, filopodia and chemotactic motility, while IRSp53 null mice display defective wound healing. Thus, IRSp53 dampens barbed end growth. CDC42 activation inhibits this activity and promotes IRSp53-dependent recruitment and clustering of VASP to drive actin assembly. These events result in spatial restriction of VASP filament elongation for initiation of filopodia during cell migration, invasion, and tissue repair.
Gesehen am 17.12.2020